Etika Pendidik dalam al Quran (Kajian Surah ‘Abasa) - Rizqa Ramadhani Lubis; Achyar Zein; Syamsu Nahar (UIN Sumatera Utara Medan, 2019)
Abstract: This research based on interest of researcher to research about ethics of educator in the Alquran. Surah ‘Abasa means He frowned, Surah ‘Abasa is classification from surah Makkiyah, surah 80th composed of 42 verse. Researcher will review and analyze viewpoint Alquran in surah ‘Abasa about educator etiquette, values of educator, ethics urgency for educator and relevance ethics of educator towards modern education. As for this research is qualitative research in design library research and because all who want to be researched are sourced from the literature and this study use tahlili interpretations. The result of this study analyze thinking about Ethics of educator in the Aquran (study surah ‘Abasa) first an educator has a good religious character (diniyah) and the educator has a noble character (akhla-qiyah). Second, the urgency of educators in surah Abasa, namely an educator can provide and express to educators to be a good role model for students. The third is the ethical relevance of educators to this modern age, that many of the problems that have occurred in the past five years are very worrying because a few of them are inappropriate to be called educators with their behavior and cannot be a role model for students.